Scalable Thirteen-Level Hybrid Multilevel Inverter Using Reduced Components - Routray A.; Sonkar S.P.; Kumar Singh R.; Mahanty R. (My University, 2025)
In this paper, a scalable thirteen-level hybrid multilevel inverter (HMLI) using reduced number of circuit components is proposed. The proposed HMLI uses single dc voltage source and two capacitors to generate thirteen voltage levels. The proposed converter is capable of generating thirteen (or even higher) voltage levels using reduced number of circuit components such as switches, diodes, capacitors, and dc sources. The capacitor voltage balance is achieved without any additional circuit, which simplifies the switching algorithm. The peak inverse voltage (PIV) and total blocking voltage (TBV) and of the converter reduces. Comparison among the proposed and other some similar existing topologies have been carried out to exhibit the improvements in the proposed HMLI; in terms circuit components, TBV, PIV, and cost function. The proposed HMLI is validated through experimentation in this work. © 2020 IEEE.